Killing others: a natural history of ethnic violence - Lange, Matthew (Cornell paperbacks, 2017)
The nature and nurture of ethnic violence -- Modernity and ethnic violence -- Teaching peace or violence? -- The origins of ethnic consciousness -- The origins of ethnic pluralism -- Emotional prejudice and ethnic obligations : motives of ethnic violence -- States and ethnic violence : containing violence or instigating unrest? -- From worst to first : declining ethnic violence in early modernizers -- Modernity and ethnic violence in Africa, Asia, and Latin America -- The future of ethnic violence